Post-Divorce Maintenance: Rethinking and Re-examining the Islamic Discourse in Pakistani Context - Rizvi, Aatir; Hafiz Muhammad Afzaal (Al-Irfan, 2022)
Maintenance is right of a woman, which has been acknowledged and protected by Sharia as well as, Pakistani law. However, there are divergent views on the post-divorce maintenance especially Hanafi scholars do not recognize it therefore in Pakistan it is still not granted to a divorced wife. Pakistan is not a welfare state and due to this, such women in many cases are left vulnerable. Further, joint family system is taking its last breaths in the Country, which also makes it difficult for divorced woman to sustain and maintain herself, especially when she is house bound or illiterate, unable to do job. There is no legal provision acknowledging mata’at-ul-talaq in Pakistan whereas, although Pakistani courts have been very progressive when it comes to protecting women rights in marriage and allied matters, yet they are hesitant to re-interpret and introduce it into Pakistani legal system, unless parliament introduces any law on the point. This article gives a brief introduction to the concept of post-divorce maintenance, views of different schools in this regard and builds a case for its award in Pakistan by quoting examples from other Muslim jurisdictions which directly or indirectly acknowledge it.